Modeling of Cultural Effect on School Autonomy at Religion-Based School in Indonesia (Jurnal Pendidikan IPA Indonesia, 2018)
School culture may have an influence on the school community. Effective school culture leads to success in accordance with values, professionalism and building school autonomy. This research aimed to develop a model of school culture that has an impact on the school autonomy. The subjects were school foundation committees, principals, teachers, staff, and students. The study was conducted in four private junior high schools managed by the Muhammadiyah foundation in Indonesia. Data were collected through interviews, questionnaires, and documentation. School culture consists of formal, sociable-dynamic, and prosperity sub-components. The results showed that culture (Cul) influenced school autonomy (Kms) in 2 ways, direct and indirect effect. The direct effects scored 0.002 and 0.32 for the indirect effect. It meant that culture gave a small contribution (0.32%) to create school autonomy while the other 0.99% came from other factors. Schools culture provided a role play to create school autonomy. Those establishing the independence of Muhammadiyah schools are formal, sociable dynamic, and prosperity. School culture contributed to the effectiveness of school management and developed positive internal habits resulting in effective and efficient school goals.